2019
DOI: 10.1371/journal.pone.0216721
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticancer potential of Thai medicinal herb extracts against cholangiocarcinoma cell lines

Abstract: Although cholangiocarcinoma (CCA) has a low incidence globally, this is extremely high in Northeast Thailand. The lack of both early detection measures and effective therapeutic drugs is the major problem for the poor prognosis of CCA patients. Based on regional knowledge, it would be advantageous to search for effective natural phyto-products for the treatment of CCA. Cardiospermum halicacabum L., Gomphrena celosioides Mart. and Scoparia dulcis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Therefore, CA was shown to have more inhibitory effect on KKU-213 cell growth compared with KKU-100 ( Figure 1). The IC50 of CA was slightly higher than that of the ethanolic extract of Scoparia dulcis (ESD) on KKU-213 of both treatments for 48 and 72 h compared to our previous study [12]. spectra were aligned, normalized and the scaling aligned in MATLAB software (Mathworks Inc., Natick, MA, USA).…”
Section: Ca Inhibits Cca Cell Growth In a Dose Dependent Mannermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CA was shown to have more inhibitory effect on KKU-213 cell growth compared with KKU-100 ( Figure 1). The IC50 of CA was slightly higher than that of the ethanolic extract of Scoparia dulcis (ESD) on KKU-213 of both treatments for 48 and 72 h compared to our previous study [12]. spectra were aligned, normalized and the scaling aligned in MATLAB software (Mathworks Inc., Natick, MA, USA).…”
Section: Ca Inhibits Cca Cell Growth In a Dose Dependent Mannermentioning
confidence: 99%
“…It is also an intermediate in the biosynthesis of eugenol and coumarin, which show potent anticancer activities [ 10 , 11 ]. Our recent study on metabolic profiling reported a compound from ethanolic Scoparia dulcis L extract with two coniferyl alcohols with β-O-4 linkages, which could potentially induce apoptosis of CCA cells [ 12 ]. However, few studies have reported the biological activity of coniferyl alcohol on cancer inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…A cytotoxic activity test can be used as the basic principle for screening potential substances for suitability as anticancer agents. The MTT test was also used for screening anticancer activity of natural products such as Cichorium intybus, Zataria multiflora, Morus alba, Eucalyptus camaldulensis (Soltanian et al 2017), Cardiospermum halicacabum L., Gomphrena celosioides Mart., and Scoparia dulcis L (Promraksa et al 2019). The basic principle of the MTT assay test was based on the activity of mitochondria in living cells that form formazan crystalline.…”
Section: Discussionmentioning
confidence: 99%
“…The liquid extract was evaporated under a vacuum using a rotary evaporator (Buchi, Switzerland). The crude extracts of leaves and barks were separately obtained and stored at 4˚C for further analyses [16].…”
Section: Sample Preparation and Crude Extractionmentioning
confidence: 99%
“…To confirm the assignment of correlated resonances, statistical total correlation spectroscopy (STOCSY) was employed. Moreover, the resonances of interest were searched against online metabolite databases such as biological magnetic resonance data bank (BMRD) and human metabolome database (HMDB) [16]. Metabolite list is present in S1 Table in S1 File.…”
Section: H-nmr-based Metabolic Profilingmentioning
confidence: 99%